(3GdOQ GdfVjQ aj BOGH GdhRjQs - (3GdZfjej , LGO Gddg Gdajhej GdTGaYj, CHh GdGNdGU,J (B1101 (3g` s ((3eMehO UfOhai GdfGSN s)
(3ChdgG (B:s
(3MeOkG Yf ChVM SHjd GdMb hfUH Ydjg OdjdkG hHYO ajbhd GdYHO gPg ahGFO MSGf hfcGJ ai ZGjI GdHjGf jJYdb HefUH GdhRQGI GdSfi daX GdhRGQI eNJda ai GTJbGbg s
(3BNQgG (B:s
(3hbGd dGHf ebdI bO CefJ cd ef HGjY GHf GdeYJR GcJH ddfGS HPdc hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3aQZ ef JCdjagG SfI (B1101s
(3fSNI KGfjIs
(3fbdJ gPg GdfSNI ef OGQ GdcJH GdSdWGfjI Yf fSNI GdCUd GdehLhOg HgG HfeQI (B1655 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdSjGSI hGdGLJeGYs